Apart and together: the Portuguese and the Dutch as neighbours in and around Timor in the nineteenth century - Schouten, Maria Johanna Christina (2017)
The Dutch and the Portuguese, who claimed the suzerainty over diverse zones on the island of Timor, in 1859 divided the island between them in an official agreement, which subsequently underwent several adaptations. Portuguese Timor was far away from the rest of the Portuguese-controlled territories in Asia and Africa, and so it was very dependent on the Dutch East Indies, in the economical, communicational, and other respects. Influence of Dutch policy on Portuguese projects was also noticeable, such as during the term of office of Governor Afonso de Castro (1858-1863) and his projects to develop coffee cultivation. In the colonial ideologies of the Netherlands as well as the Portuguese the well-being of the natives was emphasized, though in reality the interests of the mother country were pre-eminent.